Verminderte berufliche Leistungsfähigkeit und Lebensqualität bei Patienten mit moderater bis schwerer Neurodermitis - Haufe, Eva; Schäkel, Knut (Der Hautarzt, 2018)
BackgroundClinical registries may provide high-quality evidence on the use and effectiveness of therapeutic interventions under real-life conditions. Adults with moderate-to-severe atopic eczema (atopic dermatitis [AD]) are enrolled into TREATgermany and prospectively followed over at least 2 years. This paper analyses the association between dermatological quality of life and work limitations.Materials and methodsTreatment modalities and a broad set of physician- and patient-reported outcome measures are documented using validated instruments to assess clinical disease severity (EASI [Eczema Area and Severity Index], objective SCORAD [objective-SCORing Atopic Dermatitis]), quality of life (DLQI [Dermatology Life Quality Index]), symptoms (POEM [Patient-oriented Eczema Measure]), global disease severity, as well as patient satisfaction and work limitations including presenteeism (WLQ [Work Limitation Questionnaire]). From 06/2016 until 12/2017, 241 individuals (mean age 43 ± 15 years, 38.6% female) were enrolled at 19 recruitment centers; 69% of the patients were employed.ResultsEmployed persons had DLQI and WLQ scores of 10.6 ± 6.9 points and 17.7 ± 18.1%, respectively. Mean presenteeism was substantial accounting for 9.2%. With coefficients of 0.39 and 0.33 WLQ and presenteeism scores significantly correlate with DLQI (p < 0.000). Bootstrapped regression models showed that the limitations in coping with work requirements increase by 1.7% as DLQI increases by one point. Lower quality of life due to AD is most strongly associated with limitations in the area of physical and performance requirements in general. Presenteeism increases by 0.5% as DLQI increases by one point.ConclusionModerate-to-severe AD has substantial adverse economic impact with mean productivity loss of patients of almost 10%. Future analyses from TREATgermany will address the impact of innovative treatment modalities on quality of life and work productivity of patients with moderate-to-severe AD.